THE EFFECTIVENESS OF MIND MAPPING TECHNIQUES IN ENHANCING READING COMPREHENSION AND IDEA ORGANIZATION FOR 7 th -GRADE LEARNERS - Po‘latova Farangiz Furqatjon qizi; Azimbayeva Dilafruz Abdujabbarovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article explores the effectiveness of mind mapping as a strategy for improving reading comprehension and idea organization among 7th-grade students. It discusses the limitations of traditional reading instruction methods and emphasizes the importance of helping learners identify main ideas, supporting details, and relationships between concepts. Grounded in cognitive learning theory, mind mapping is presented as a visually engaging technique that enhances understanding, memory retention, and active participation. The article describes how students who create mind maps during reading lessons demonstrate improved comprehension, summarization, logical organization, and academic writing skills. In addition to supporting reading development, mind mapping is shown to be an effective tool for note-taking, essay planning, exam preparation, presentations, and problem-solving. Although initial guidance from teachers is necessary, consistent practice leads to greater independence and confidence among learners. Overall, the study concludes that mind mapping is a highly beneficial instructional approach that fosters critical thinking, motivation, and long-term academic success. Abstract: This article explores the effectiveness of mind mapping as a strategy for improving reading comprehension and idea organization among 7th-grade students. It discusses the limitations of traditional reading instruction methods and emphasizes the importance of helping learners identify main ideas, supporting details, and relationships between concepts. Grounded in cognitive learning theory, mind mapping is presented as a visually engaging technique that enhances understanding, memory retention, and active participation. The article describes how students who create mind maps during reading lessons demonstrate improved comprehension, summarization, logical organization, and academic writing skills. In addition to supporting reading development, mind mapping is shown to be an effective tool for note-taking, essay planning, exam preparation, presentations, and problem-solving. Although initial guidance from teachers is necessary, consistent practice leads to greater independence and confidence among learners. Overall, the study concludes that mind mapping is a highly beneficial instructional approach that fosters critical thinking, motivation, and long-term academic success.